Introduction to general, organic and biochemistry in the laboratory - Hein, Morris (Pacific Grove, California : Brooks/Cole Publishing Company, 2001)
This manual is intended for the student who has not had a course in chemistry.
Laboratory manual to accompany: Introduction to general, organic, and biochemistry.